Gestão e gerenciamento dos resíduos eletrônicos do setor de informática em agências governamentais do estado do Espírito Santo - Jesus, Roger Trancozo de (2023)
Government agencies (AG) are consumers of computers such as workstations, notebooks, printers, since the execution of their activities depends directly on the use of information and communication technology equipment (ETIC). Consequently, waste information and communication technology equipment (RETIC) largely makes up the amount of waste electrical and electronic equipment (WEEE) generated by AG. At the end of the useful life cycle of WEEE of AG, although Brazil has a Federal Decree that determines the mandatory destination of WEEE of domestic origin for reverse logistics systems (SLR), controversially, exclude WEEE of governmental origin. The literature about management of RETIC of AG has shown that the theme has little approach, and it is necessary to complement it with studies that address higher education institutes (HEIs) as public agencies. A survey on the barriers to WEEE management in AG showed that several developing countries share barriers related to the absence of specific legislation, ignorance of the potential problems that WEEE can cause to the environment and human health, among others. Opportunities for RETIC management were identified from the survey of barriers, and the increase in the useful life cycle, by postponement of ETIC substitutions or by the reuse of RETIC, were the most pointed out by the literature. In addition, a visit to the Center for Discard and Reuse of Informatics Residuals (CEDIR) of the University of São Paulo (USP) provided elements for the elaboration of a proposal for the creation of a Primary Processing Center (CPP) of RETIC of the Government in the State of Espírito Santo (ES). A survey on the acquisitions and write-offs of the ETIC and RETIC of the Government of ES was carried out from the database of movable property movements of the State Secretariat of Management and Human Resources (SEGER) to demonstrate the potential of generating RETIC in the State. It was found the generation of 31ton/year of RETIC in the Government of ES, where each public server was responsible for 1.05 kg/year of generation of this waste. These data allowed us to compare the generation of RETIC with other studies in HEIs and AG.